Marriage material how an enduring institution is changing same-sex relationships - Ocobock, Abigail (The University of Chicago Press, 2024)
"In the US, marriage rates are at an all-time low. But as rates are declining, a considerable portion of the US population only very recently has the right to marry: same-sex couples. Do same-sex couples follow widespread trends of couples turning away from marriage? And how does the expansion of marriage to include same-sex couples change the meaning of the institution in society?"